Implementasi dan Implikasi Peraturan Daerah Kabupaten Sampang Nomor 7 Tahun 2019 tentang Madrasah Diniyah Takmiliyah - Ismail, Ismail; Zainullah, Zainullah; Tamam, Nurul (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2022)
This study refers to qualitative research methods, the data analysis was carried out by means of data reduction, data presentation, and verification and drawing conclusions. This research resulted in: (1) Implementation of this regional regulation in the form of: (a) Provision of Assistance for Organizing Diniyah Education and Private Teachers (BPPDGS); (b) Madrasah diniyah stakeholder synergy; and (c) Community Involvement in Strategic Policy Formulation; (2) This regional regulation has implications for madrasah diniyah in the form of: (a) institutional strengthening; (b) improving the quality of learning processes and outcomes; and (c) to become an instrument for realizing the vision and mission of the Sampang government